Antimicrobial Effect of Garlic (Allium sativum) and Thyme (Zataria multiflora Boiss) Extracts on Some Food Borne Pathogens and Their Effect on Virulence Gene Expression - El-Azzouny, Mona M; El-Demerdash, Azza S; Seadawy, Hanan G; Abou-Khadra, Sally H (Cellular and Molecular Biology, 2018)
The incrementing scope of pathogenic resistance to antibiotics has encouraged the search for antivirulence natural extracts. Therefore, our study designed to demonstrate the antimicrobial activity of an aqueous-garlic and thyme oil extracts against Gram-positive (Staphylococcus aureus) and Gram-negative (Salmonella spp.) bacteria by evaluating the influence of sub-inhibitory concentrations on the expression of the most critical virulence genes of the tested isolates. The antibacterial potential of both herbs was checked by the agar well diffusion method and minimum inhibitory concentration (MIC) assay. Interestingly, all isolates were inhibited by both extracts up to 50% concentration. Also, the MIC values of garlic extract (0.125-1µg/ml) against Salmonella isolates were lower than the values of thyme extract (0.5- 8µg/ml). But in S. aureus isolates, the MIC values of thyme extract (0.25- 2µg/ml) were the lowermost. Conventional PCR investigated that all S. aureus isolates carried the hlg (hemolysin) and icaA (intracellular adhesion) genes, but only six Salmonella isolates (three S. typhimurium and one each of S. kentucky, S. anatum, and S. lagos) had both the sopB (Salmonella outer protein B) and mgtC (membrane protein) genes. Real-time RT-PCR assays were performed to evaluate the extract's effect on the virulence genes. The thyme-oil extract has significantly repressed S. aureus virulence genes expression more than aqueous-garlic extract, which later one has effectively more than thyme-oil extract in downregulating the Salmonella virulence genes. In conclusion, garlic and thyme extracts can be used not only as a flavor, but also as potential antimicrobial agents against Gram-positive and negative bacteria.